Islam and Sustainable Development Goals (SDGS) Gender Equality in Perspective of Nasaruddin Umar and Musdah Mulia - Prayitno, Prayitno (Jurnal Locus Penelitian dan Pengabdian, 2025)
This research explores the concept of gender equality through the lens of two prominent Indonesian Islamic thinkers—Nasaruddin Umar and Musdah Mulia—framed within the context of Sustainable Development Goal 5 (Gender Equality). Employing a qualitative, comparative literature-based methodology with a hermeneutic approach, the study analyzes primary sources authored by both figures alongside secondary literature on gender and SDGs. Findings indicate both thinkers agree that the Qur’an recognizes distinctions between men and women without condoning discrimination. They both cite foundational verses (e.g., QS 49:13, 16:97) to argue that gender equality is a core Islamic value, supporting the notion that differences should foster harmony, not hierarchy. However, Nasaruddin's work contributes an in-depth analysis of ten interpretive biases rooted in linguistic and cultural factors, while Musdah emphasizes monotheism (tawhid) as the foundation of equality and critiques patriarchal misinterpretations. This study contributes a novel perspective by connecting Islamic gender ethics with the global SDG agenda, particularly within Muslim-majority societies. It argues that contextual reinterpretation of religious texts and alignment with universal development goals can foster inclusive and equitable social transformation. Thus, the research presents a culturally adaptive model to support SDG 5 through Islamic teachings.